2010
DOI: 10.1007/s00464-010-1203-y
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term outcome after endoscopic stent therapy for complications after bariatric surgery

Abstract: Although bariatric surgery effectively reduces the mortality risk from obesity-related comorbidities [1,2], it is associated with a 1-5% risk of anastomotic complications. Anastomotic leaks have traditionally been treated with a combination of drainage with long-term parenteral nutrition or postanastomotic enteral nutrition, allowing the leak to heal. Strictures at the gastrojejunostomy are initially treated with repeated endoscopic dilation, but revisional bariatric surgery is needed for refractory strictures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Despite the novel double-bump structure of the Beta stent, which has specifically been designed to prevent migration, migration occurred in 32% of patients (26% of stents) in this study. This seems comparable to the results of other fully covered stents, with a migration rate of 18–67% in previous studies [8, 11, 16, 17, 19, 20]. Partially covered stents are less prone to migration with a migration rate of 5–15% [7, 10, 14, 15, 18].…”
Section: Discussionsupporting
confidence: 88%
“…Despite the novel double-bump structure of the Beta stent, which has specifically been designed to prevent migration, migration occurred in 32% of patients (26% of stents) in this study. This seems comparable to the results of other fully covered stents, with a migration rate of 18–67% in previous studies [8, 11, 16, 17, 19, 20]. Partially covered stents are less prone to migration with a migration rate of 5–15% [7, 10, 14, 15, 18].…”
Section: Discussionsupporting
confidence: 88%
“…Mainstays of laparoscopic or open re-exploration follow the principles of drainage, creation of a controlled fistula with drains, antimicrobial therapy, parenteral nutrition or enteral nutrition with consideration of feeding access of the jejunum either with a nasoenteric catheter placed beyond the area of leak or gastrostomy-tube placement in the gastric remnant Limited data are available in the form of case reports and small case series of the use of biologic tissue sealants as well as the use of endoscopic stent placement for a gastrojejunal leak [50][51][52]. Further research may be helpful in refining the application of these technologies,.…”
Section: Radiologic Evaluation Vs Surgical Exploration For Suspectedmentioning
confidence: 99%
“…opined that earlier stenting might further decrease mortality and morbidity of post-operative leaks in the future. [8] Various studies have demonstrated healing rates for oesophageal/post-operative leaks in the range of 94%[1920] - 32 %. [21] Even in long-standing perforations, those who would otherwise undergo oesophageal resection can still be good candidates for stent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[12] The main morbidity of covered stents is thought to be migration while that for uncovered stents was tissue in-growth and difficult extraction. [20] Covered metal stents can be removed safely in most patients with a low complication rate and are available with a larger diameter than silastic stents, allowing a water-tight bypass of the leak site. [25] In a small series of 6 patients using SEPS for anastomotic leaks arising from Roux-En-Y gastric bypass, Edwards et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation